Characteristics of suicidal emergency room patients before and during the COVID‐19 pandemic in Japan - Kyohei Otani; Ryohei Yoshikawa; Atsumi Naitou; Haruko Fukushima; Kunitaka Matsuishi (Wiley, 2023)
Abstract Aim Owing to the stress caused by the behavioral restrictions and lifestyle changes during the COVID‐19 pandemic, suicide rates have increased in Japan, especially among young people. This study aimed to identify the differences in the characteristics of patients hospitalized for suicide attempts in the emergency room, requiring inpatient care before and during the pandemic over 2 years. Methods This study was a retrospective analysis. Data were collected from the electronic medical records. A descriptive survey was conducted to examine changes in the pattern of suicide attempts during the COVID‐19 outbreak. Two‐sample independent t‐tests, Chi‐square tests, and Fisher's exact test were used for data analysis. Results Two hundred one patients were included. No significant differences were found in the number of patients hospitalized for suicide attempts, average age, or sex ratio before and during the pandemic periods. Acute drug intoxication and overmedication in patients increased significantly during the pandemic. The self‐inflicted means of injury with high fatality rates were similar during the two periods. The rate of physical complications significantly increased during the pandemic, while the proportion of unemployed individuals significantly decreased. Conclusions Despite studies predicting an increase in suicides based on past statistics of young people and of women, no significant changes were observed in this survey of the Hanshin‐Awaji region, including Kobe. This may have been owing to the effect of suicide prevention measures and mental health measures implemented by the Japanese government after an increase in suicides and after past natural disasters.